Biomedical Signal and Image Processing - Zhou, Yongxia (Biomedical Engineering, 2021)
This book examines the principles and applications of biomedical imaging and signals processing as well as the advances of multimodal imaging and multi-feature quantification for disease diagnosis and treatments in ophthalmology, stroke, chemotherapy, and neurology. Chapters cover such topics as image segmentation and registration, feature selection for classification, micro-texture characterization, simulation of tissue deformation, and high-level statistical analyses. The chapters also discuss different imaging modalities including MRI and EEG, confocal microscopy, and molecular imaging for improving the accuracy of disease detection via higher spatiotemporal resolution and better illustration. Overall, the book provides a comprehensive review of biomedical imaging and signal processing, informing readers with current and insightful knowledge in these fields.